“Zooming” in strategies and outcomes for trauma cases with Injury Severity Score (ISS) ≥16: promise or passé? - Doklestić,Krstina (2022)
SUMMARY OBJECTIVE: Rescuing severe trauma cases is extremely demanding. The present study purposed to analyze the efficiency of trauma management at Emergency Centre, University Clinical Centre of Serbia, Belgrade, included outcome within 28 days. METHODS: This retrospective study involved 131 intensive care unit trauma cases with total Injury Severity Score ≥16, in terms of administrating the two strategies: (i) definitive surgical repair and (ii) damage control laparotomy. RESULTS: The damage control laparotomy cases revealed statistically higher Injury Severity Score and APACHE II scores, significant brain dysfunction, and hemorrhagic shock on arrival (p<0.001). In addition, the damage control laparotomy had a higher rate of respiratory complications, multiple organ deficiency syndrome, and surgical wound complications (p=0.017, <0.001, and 0.004, respectively), with more days on mechanical ventilation (p=0.003). Overall mortality was 29.8%. Although higher early mortality within ≤24 h in the damage control laparotomy (p=0.021) had been observed, no difference between groups (p=0.172) after the 4th day of hospitalization was detected. CONCLUSIONS: Trauma patients have a high mortality rate in the 1st hours after the incident. Compelling evidence linking host and pathogen factors, such as mitochondrial apoptosis pathways, appears to correlate with loss of organ dysfunction, both cytopathologically and histopathologically. Adequate selection of patients necessitating damage control laparotomy, allowed by the World Society of Emergency Surgery, abdominopelvic trauma classifications, and improvements in resuscitation, may improve the results of severe trauma treatment.